Alexander Technique To Reduce Lower Back Pain In 3rd Trimester of Pregnancy - Ratu Safitri Ramadhania; Ribkha Itha Idhayanti; arum lusiana (Midwifery and Nursing Research, 2020)
Background  : Studies back pain due to pregnancy 25-90%, was estimated 50% of pregnant women experience back pain. As many as 80% of pregnant women said that back pain during pregnancy interfere with daily routines and 10% unable to work. The Alexander Technique exercises 65-72% effective in reducing back pain. Learning the Alexander technique have an impact on long-term reductions significantly to lower back pain. Research to determine the effectiveness of the Alexander Technique to the level of lower back pain in the third trimester pregnant mothers.Method : pre-experimental research with one group pretest posttest design. Population this study the third trimester pregnant women who experience lower back pain amounting to 31 people in Selopampang public health center Temanggung district. Collecting data used a pain scale observation sheet NRS (Numerical Rating Scale). Analyze data used Wilcoxon test.Result : research showed the Z value of -3.859. It showed that the Alexander technique is effective in reducing low back pain that is felt as much as 3x with Asymp. Sig. (2-tailed) 0.000, which means there is a difference low back pain before and after alexander technique intervention.Conclusion : the Alexander Technique could be an alternative to reduce lower back pain in 3rd trimester of pregnancy